Barriers And Opportunities In Developing ‘do-it-yourself’ Products For Low-income Housing - Santos, Aguinaldo Dos; Rocha, Cecilia G. da; Lepre, Priscilla (Penerbit Universiti Sains Malaysia, 2010)
Direct involvement of the user in the assembling process of his/her own products or even entire house is a reality among low-income populations in developing countries. Nevertheless, there are a limited number of products that have actually been designed from a do-it-yourself (DIY) perspective, which results in several problems, such as poor user safety while the product is being assembled or inadequate results from an improvised assembling. Hence, the main goal of this paper is to analyse barriers to and opportunities for developing DIY products for low-income housing in developing countries. The research method utilises a case study of a DIY product consisting of a hybrid solution that acted as both a partition wall and a wardrobe. The identified opportunities included more systematic use of existing craft competencies among low-income families and the possibility of cost reduction through DIY concepts. Major barriers included the perception of the DIY product as inferior and the difficulty of communicating the DIY assembly process to users who quite often are illiterate.